Integrated ABC/VEN-analysis of medicinal prescribing in pharmacotherapy of bronchial asthma in children - I. A. Kostiuk; K. L. Kosiachenko (Zaporozhye State Medical University, 2019)
Nowadays, medical institutions pay great attention to optimizing the medicine provision of inpatients. A significant range of medicines, which are registered in Ukraine and are used for the treatment of bronchial asthma (BA) in children, require improving the system of their selection for a particular department in conditions of optimal use of limited funds. Aim. The aim of the work is to assess the expense rationality of BA pharmacotherapy in children by the results of ABC/VEN-analysis. Materials and methods. Retrospective analysis of historical data of medical records in patients with the main diagnosis of BA, ABC/VEN-analysis. Results. For the economic evaluation of the rational medicine usage, an ABC-analysis was performed, which made it possible to rank medical prescriptions by level of consumption. Group A (80 % of costs) was formed by 14 international non-proprietary names (INN) (11.2 % of the total INN number), Group B (15 % of costs) - 25 INN (25.2 %), and Group C (5 % of the cost) - 61 INN (63.6 %). Formal VEN-analysis revealed the ratio of indices for INN, trade names and the number of medical prescriptions, which were 3:27:41; 11:74:102 and 411:768:618 respectively. It was established that during 2018 the largest part of group A expenditure was occupied by the segment of essential medicine (54.7 %), and vital - only 17.9 %, which indicates the need to further optimize the drug supply for children with asthma. Conclusions. The results of the conducted research demonstrate the need to improve the medicine provision of children with asthma, and can be used to make management decisions, purchase medicine by healthcare institutions and reduce the cost of pharmacotherapy by increasing the share of domestic medicine.